The Impact of Social Support and Emotional Regulation on Career Adaptability: Exploring the Role of Self-Control as an Intervening Variable among Final-Year Psychology Students at Tjut Nyak Dhien University - Lubis, Indah Sari (Journal of Ecohumanism, 2024)
The aim of this study is to examine and analyse how social support and emotional levels influence career adaptability through self-control as an intervening variable. The study subjects are 100 students from the Psychology Department at Tjut Nyak Dhien University. The independent variables are social support and emotional levels, while career adaptability is the dependent variable, with self-control acting as the intervening variable. Data analysis was conducted using Structural Equation Modelling (SEM) with SMART PLS 4.0 software. Data collection techniques included questionnaires, observation, and document review. The research utilized a quantitative descriptive method, employing SEM for data analysis. The population and sample for this study consisted of 100 students, and sampling was conducted using a census method. The findings indicate that, partially, social control and emotional effectiveness have a significant influence on the career adaptability of Psychology students at Tjut Nyak Dhien University, and they also impact self-control. Simultaneously, social control and emotional effectiveness affect career adaptability through self-control as an intervening variable. The study concludes that increasing social support can enhance students' abilities at the Psychology Department of Tjut Nyak Dhien University. Furthermore, students' emotional regulation will improve, enabling them to better control their actions during the process of adapting to career development. This highlights the critical role of both social and emotional factors in shaping students’ career adaptability, mediated by their ability to maintain self-control.